SAT0445 TRABECULAR BONE SCORE IMPROVES FRACTURE RISK STRATIFICATION IN PATIENTS WITH REDUCED BONE MINERAL DENSITY. (13th June 2020) - Rakieh, C.; Ho, S.; Butler, R.
Abstract : Background: Trabecular bone score (TBS) is a textural index of bone microarchitecture and has been found to be related to 3D bone structure. A number of cohort studies have demonstrated the value of TBS as an independent fracture risk in clinical trials. Yet, very little is known about the performance and clinical value of TBS in real life practice. Objectives: To investigate the sensitivity and specificity of TBS in identifying prevalent fractures when compared with bone mineral density (BMD) measured by DXA. To evaluate the added value of TBS in fracture risk prediction above that obtained from DXA. Methods: Consecutive patients aged ≥ 18 with BMI 15-37 attnding a DXA plus TBS assessment were considered eligible. Sensitivity, specificity, and area under the curve (AUC) for prevalent major osteoporotic fracture (MOF) and clinical vertebral fractures (VF) were assessed for the following parameters: BMD lowest T-score ≤-2.5 (neck of femur, total hip, or spine), TBS T-score ≤-2.5, and either TBS or BMD T-score ≤-2.5. BMD categories (normal, osteopenia, and osteoporosis) were stratified by TBS T-score: normal (T-score ≥-1), moderate (-1≥T-score≥-2.5), and degraded TBS (T-score ≤-2.5) resulting in 9 risk groups. Odds ratios were calculated for all risk categories and fracture prevalence was compared between the best and worst TBS strata at each BMD level using chi-square test. Results: 540 patients (87% females, 68.1 ± 11.6 years) were included. 238 (44%) had MOF including 81 (15%) clinical VF. For MOF, BMD had higher sensitivity (49.6% vs 30.7%), lower specificity (68.2% vs 82.1%), and similar AUC (0.59 vs 0.56) versus TBS. For VF, the sensitivity, specificity and AUC for BMD were 60%, 64%, and 0.62 respectively versus 42%, 79.7%, and 0.61 for TBS. Combining TBS and BMD (either T-score ≤ -2.5) increased the sensitivity to 63% for MOF and 75.3% for VF without affecting AUC (0.6 and 0.64 respectively). Patients with osteoporosis and degraded TBS had the highest OR of 2.65 for MOF and 3.8 for VF. The fracture risk increased at the same level of BMD when TBS was degraded. Numerically, the risk of MOF increased steadily from strata 1 to 9 and was statistically significant for osteoporosis with degraded TBS and osteoporosis with moderate TBS. When both TBS and BMD were normal, the risk of fracture was significantly reduced. In the osteopenia and osteoporosis BMD categories, patients with degraded TBS had significantly higher prevalence of fracture compared to those with normal TBS in the same BMD category. Conclusion: Fracture risk stratification can be improved when TBS is added to BMD. The sensitivity of predicting fracture may also improve when TBS and BMD are combined. Patients with both normal TBS and BMD have the lowest fracture risk, whereas those with degraded TBS and osteoporosis have the highest risk of fracture and should be targeted for early or more aggressive treatment. References: [1]Hans D et al. J Bone Miner Res. 2011;26(11). [2]McCloskey EV et al. Calcif Tissue Int. 2015;96(6). Acknowledgments: Bone density team, Robert Jones and Agnes Hunt Orthopaedic Hospital Disclosure of Interests: None declared